Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbasis Media Questin Card Terhadap Kemampuan Berfikir Kritis Dan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Di MA NW Bungtiang - Rohnil Rohnil; Isfi Sholihah; Dewi Dara Surya Ningsih; Durratul Yatimah; Ellsa Dian Safira (Universitas Hamzanwadi, 2024)
This study aims to see the effect of using Question Card-based Problem Based Learning (PBL) model on critical thinking skills and student learning outcomes in Economics subject at MA NW Bungtiang. Specifically, the study examines: (1) the effect of Question Card-based PBL implementation on critical thinking skills, (2) the effectiveness of Question Cardmedia in improving student learning outcomes, and (3) whether there are differences in critical thinking skills and student learning outcomes between PBL-based learning and conventional methods. This type of research uses a quasi-experimental approach with a One-Shot Case Study design. The research subjects were all 21 students of class XI IPS, determined by saturated sampling technique. The research instruments consisted of tests and questionnaires, while the data collection method used classical assumption tests, simple linear regression, and hypothesis tests. Based on the results of the study, it shows that Question Card-based PBL has a significant effect on both critical thinking and learning outcomes. The score for critical thinking skills increased by 0.900 points (t-count 7.649 > t-table 1.990) and learning outcomes increased by 0.904 points (t-count 4.572 > t-table 1.990). The coefficient of determination showed a contribution of 75.5% to critical thinking skills and 52.4% to learning outcomes. These findings confirm that PBL with Question Cards is effective in training students' analysis, argumentation, and problem-solving.